The restoration of the Nativity Church in Bethlehem
1 online resource
Keywords: "This book is a summary of the main restoration works carried out at the Church of the Nativity in Bethlehem that commenced in September 2013. The book is addressed to a generic reader interested in the history and conservation of one of the most representative examples of our heritage, but also, in light of its technical and scientific value, to university students, technicians, restorers, architects, structural engineers, archaeologists and historians"--